Cost estimation and sensitivity analysis of a latent thermal energy storage system for supplementary cooling of air cooled condensers. (15th August 2018) - Pan, Chunjian; Vermaak, Natasha; Romero, Carlos; Neti, Sudhakar; Hoenig, Sean; Chen, Chien-Hua; Bonner, Richard
Highlights: A novel phase change material (PCM) based cooling application is proposed. A modeling method for a finned heat pipe assisted PCM system in 3D is developed. Optimal design and cost sensitivity analysis of the system are presented. Abstract: As a booming economy drives the need for more electricity, demands on freshwater for thermoelectric power generation also grow. Facing the limited freshwater resources, alternative dry cooling technologies that reduce water consumption are becoming more prevalent. However, the performance of air cooled condensers (ACCs) is seriously deteriorated at ambient temperature. To address this challenge, a novel application of a Phase Change Material (PCM) based cooling system for supplementary cooling of ACCs is proposed. In order to evaluate the system cost, a solidification modeling approach called a Layered Thermal Resistance (LTR) model is extended to 3D in cylindrical coordinates for the first time. The LTR model efficiently estimates the behavior of a finned heat pipe module for the PCM-based cooling system. In the present work, a new nonlinear optimization problem is formulated, based on the LTR model, to estimate system cost and conduct sensitivity analysis. Overall, it is found that the material cost of the finned heat pipe-assisted PCM tank is around 30 $/kW for a 10-h solidification time requirement, which is a promising cost for the system to be accepted in the market. Based on the sensitivity analyses, it is found that the latent energy of the PCM has first-order impact on the system cost.